A human rights based approach to project induced displacement and resettlement. Issue 1 (2nd January 2017) - van der Ploeg, Lidewij; Vanclay, Frank
Abstract: Respecting, protecting and fulfilling human rights must become more prominent in both the processes and outcomes of resettlement. We have developed a Human Rights-Based Approach to Resettlement for use by project operators, rights holders and governments so that they can better understand what the corporate responsibility to respect human rights entails in situations of involuntary resettlement and expropriation. We outline the procedural human rights principles and resettlement outcomes that must be achieved in order for resettlement to be considered human rights compliant. We also consider how human rights are addressed in the International Finance Corporation Performance Standard 5 on land acquisition and involuntary resettlement. We suggest that the International Finance Corporation's largely silent approach towards the private sector's human rights responsibilities potentially understates the significant human rights risks that characterize displacement and involuntary resettlement.